Death by wheat-loaded cartridge: a case report - Okdemir, Erdem; Keten, Alper (The American journal of forensic medicine and pathology, 2019)
The materials used to produce shotgun ammunition can have different properties depending on the purpose, and ammunition can be fabricated or loaded manually. In Turkey, wheat-loaded cartridges are manufactured for use as sound cartridges. This ammunition is understood by the public to be harmless. However, we present a case of a 13-year-old adolescent boy who was wounded from a contact shot to the chest. An entrance wound measuring 7 cm and 5 cm in diameter was seen on the skin. Wheat grains could not be detected in the internal organs and were only observed between the chest muscles around the entrance wound. A plastic wad was also found in this area. The cause of death was internal bleeding due to internal organ injury. Wheat-loaded cartridges are not visible on x-ray and are difficult to detect visually in the wound.